Foundations of a Successful Site Quality Management System - Muhammad Waheed; Mutahir Abbas (Indonesian Journal Of Civil Engineering Education, 2023)
Abstract: When it comes to consistently giving clients value and quality, the construction industry is essential. But the industry has been having problems with quality, which has resulted in subpar work, dangerous setups, and overspending. Establishing a Quality Management System (QMS) is important for solving these issues. The QMS offers an organized method for controlling the quality of processes and products, providing client satisfaction, adhering to legal requirements, and minimizing loss and rework. Good quality management system (QMS) implementation requires doing things like Company assessment, preliminary planning, awareness-raising, Progressive enhancement, measurement and control, auditing, specialist instruction, control of records, and distribution. Through data analysis from questionnaires and interviews with builders/contractors, consultants, and customers/building occupants, as well as an examination of small-scale building contractors' quality management practices and their effects on cost-effectiveness, organizational effectiveness, and customer satisfaction, the purpose of the research is to highlight the importance of quality management during the minimal building development the undertaker's executing stage.